Sistem Informasi Manajemen Pada Jasa Expedisi Pengiriman Barang Berbasis Web - Cahya Vikasari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
The freight forwarding service is a promising business so many new companies are opening this business. Business Delivery of goods is the impact of other businesses that require services expedition. Some of the problems that can happen is data loss, data error or lack of complete data delivery of goods, the division of work courier is also a complicated matter, and tracking of the delivery of goods is difficult. Application development to overcome the problem is building information management of web-based freight forwarding with waterfall software development method and using the concept of Unified Modeling Language (UML). Use of the application can reduce the risk of data loss due to less orderly administration, error data or lack of data delivery of goods because the data is stored centrally on the server. Distribution of courier in goods delivery can be done more easily. Use of this application provides information about tracking the delivery of goods so that the delivery process can be tracked its existence